2002
DOI: 10.1038/sj.onc.1205137
|View full text |Cite
|
Sign up to set email alerts
|

MDMX stability is regulated by p53-induced caspase cleavage in NIH3T3 mouse fibroblasts

Abstract: MDMX is a p53 binding protein, which shares a high degree of homology with MDM2, a negative regulator of the tumor suppressor p53. MDMX has been shown to counteract MDM2-dependent p53 degradation and to stabilize p53 in its inactive form. In this study: we identify two MDMX proteolytic pathways that control its intracellular levels, and show that MDMX posttranslational processing may be regulated by p53. Mouse MDMX is cleaved in vitro and in vivo by caspase activity, between aminoacids 358 and 361, producing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 47 publications
4
39
0
Order By: Relevance
“…Recently, caspase activities were found to be involved in biological events different from apoptotic death, such as the negative control of erythroid differentiation 23 and the modulation of the MDM2 and MDMX proteins in nonapoptotic cells. 33,34 Our results add evidence for a novel role of caspases, strengthening the concept that this complex net of proteases has been evolutionarily selected to accomplish multiple, different tasks in addition to cell suicide. However, whether the same caspases are involved in apoptotic and nonapoptotic functions through different mechanisms of activation or specificity, or whether caspase-like activities different from the classical apoptosis-associated caspases are responsible for these newly described, nonapoptotic functions need to be evaluated.…”
Section: Erk2 Cleavage Is Required For P53 To Inhibit Cell Proliferationsupporting
confidence: 68%
“…Recently, caspase activities were found to be involved in biological events different from apoptotic death, such as the negative control of erythroid differentiation 23 and the modulation of the MDM2 and MDMX proteins in nonapoptotic cells. 33,34 Our results add evidence for a novel role of caspases, strengthening the concept that this complex net of proteases has been evolutionarily selected to accomplish multiple, different tasks in addition to cell suicide. However, whether the same caspases are involved in apoptotic and nonapoptotic functions through different mechanisms of activation or specificity, or whether caspase-like activities different from the classical apoptosis-associated caspases are responsible for these newly described, nonapoptotic functions need to be evaluated.…”
Section: Erk2 Cleavage Is Required For P53 To Inhibit Cell Proliferationsupporting
confidence: 68%
“…Several studies reported that MDMX can be ubiquitinated by MDM2 and subsequently degraded through the proteasome after a toxic treatment in various cell lines. 35,36 Interestingly, Gentiletti et al 37 proposed that MDMX was processed by caspase-3 and subsequently degraded by the proteasome. Therefore, caspase-3 might be responsible in part for MDMX protein loss in some conditions, but not all as GLU and APP-Ab treatments do not activate caspase-3 ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although the identities of the damage sensors remain unknown, the molecular entities responsible for transducing the damage signals to specific effectors are relatively well characterized. For example, one of its roles is to act as a tumor suppressor protein that senses DNA damage and acts as a guardian of genome stability (Chernova et al, 1995;Blaise et al, 2001;Gentiletti et al, 2002). In some cases, p53 becomes a molecular signature based on the type of cancer (Hussain et al, 2000).…”
Section: Role Of P53 In Uv Irradiation-induced Dna Damagementioning
confidence: 99%